2016
DOI: 10.1007/s00359-016-1137-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a skeletal muscle titin mutation on walking in mice

Abstract: Titin contributes to sarcomere assembly, muscle signaling, and mechanical properties of muscle. The mdm mouse exhibits a small deletion in the titin gene resulting in dystrophic mutants and phenotypically normal heterozygotes. We examined the effects of this mutation on locomotion to assess how, and if, changes to muscle phenotype explain observed locomotor differences. Mutant mice are much smaller in size than their siblings and gait abnormalities may be driven by differences in limb proportions and/or by cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
0
9
1
Order By: Relevance
“…In contrast to expectations based on age-related degeneration of mdm muscles, correlation analysis (Table 1) showed that neither muscle mass nor passive stress at L 0 +10% was significantly related to age in wild-type or mdm muscles (all P>0.05). Our previous studies showed that mdm mice and their muscles are small, not because they degenerate over time, but rather because growth stops at an early age (Pace et al, 2017). In contrast to expectations based on age-related muscle degeneration, we also found that maximum isometric stress increased significantly with age (Table 1) in our sample of mdm muscles (n=7, P=0.0055) but not in wild-type muscles (n=8, P=0.2859).…”
Section: Resultscontrasting
confidence: 79%
“…In contrast to expectations based on age-related degeneration of mdm muscles, correlation analysis (Table 1) showed that neither muscle mass nor passive stress at L 0 +10% was significantly related to age in wild-type or mdm muscles (all P>0.05). Our previous studies showed that mdm mice and their muscles are small, not because they degenerate over time, but rather because growth stops at an early age (Pace et al, 2017). In contrast to expectations based on age-related muscle degeneration, we also found that maximum isometric stress increased significantly with age (Table 1) in our sample of mdm muscles (n=7, P=0.0055) but not in wild-type muscles (n=8, P=0.2859).…”
Section: Resultscontrasting
confidence: 79%
“…Compared with WT mice, mdm mice exhibit a nearly complete absence of ankle dorsiflexion at the start of the stance phase (Pace et al, 2017), despite the fact that the ankle range of motion is normal during manipulation of the joint. During walking, energy absorbed by the posterior muscles of the shank is subsequently recovered to amplify work and power during plantarflexion (Lipfert et al, 2014;Roberts and Azizi, 2011).…”
Section: Comparison Between In Vitro and In Vivo Muscle Workmentioning
confidence: 93%
“…It is interesting to consider how the deficit in negative work in mdm muscles might affect locomotor biomechanics in the mouse. Pace et al (2017) compared limb morphology and walking kinematics between mdm and WT mice. They found that differences in limb proportions (i.e.…”
Section: Comparison Between In Vitro and In Vivo Muscle Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, controlled eccentric activity immediately prior to shortening, termed a stretch‐shortening cycle (SSC) or countermovement, increases shortening force (Abbott and Aubert, ; Cavagna et al, ; Cavagna and Citterio, ; Gregor et al, ; Finni et al, 2000). An abundance of evidence suggests that elastic energy storage in tendons and titin—a large, calcium‐dependent, spring‐like protein spanning half of the sarcomere—underlies the enhanced and increased metabolic efficiency of force production during SSCs and may actually protect the sarcomeres from damage during whole muscle stretch (Edman et al, ; Roberts et al, ; Biewener et al, ; Joumaa et al, ; Leonard et al, ,b; Nishikawa et al, ; Joumaa and Herzog, ; Azizi and Roberts, ; Holt et al, ; Konow et al, ; Monroy et al, ; Powers et al, ; Pace et al, ). Indeed, Herzog and colleagues () argue that titin should be considered a third myofilament alongside actin and myosin due to its substantial contributions to force production during active fiber lengthening.…”
Section: Parameters Of Performancementioning
confidence: 99%